Cross-Cultural Communication of Foreign Students in the Indonesian Language Regarding Cultural Expressions - Ade Mulyanah; Ekaning Krisnawati (International Journal of Science and Applied Science: Conference Series, 2022)
Understanding cross-cultural communication is an important aspect of determining the success of communication. Understanding cross-cultural communication is the key to the success of communication (Griffin, 2010). Differences in cultural value orientation also cause differences in cross-cultural communication. What is considered good or bad behaviour, appropriate or inappropriate, polite or impolite in one culture is often perceived as different or contradictory to other cultures. This paper discusses cross-cultural understanding for international students regarding salutations and cultural expressions in the Indonesian language from a sociolinguistics point of view. This research uses a descriptive method. The data collection technique was done virtually by interviewing and filling out questionnaires. By applying the theory of Gudykunst (2003) and Gudykunst and Ting-Toomey (in Jati, 2013), this study quantitatively tested the impact of culture on direct and indirect communication. There are so many theories that discuss the differentiating factors in the emergence of cross-cultural communication. (Liliweri, 2009) explains that several systems cause differences in cross-cultural communication. The study results reveal that cultural expressions should consider cultural aspects in addressing people in certain cultures. The aspects emerge in the stratification of people in society by politely addressing them for those who are respected. They can give titles when addressing them in their equality, the same status, the same position, and other cultural perspectives. The use of the title Bapak/Pak, Ibu/Bu, Mbak, Mas, Adik/Dik, and Kakak/Kak need the students' cultural knowledge. Moreover, the study indicates how international students in Indonesian academic settings should understand implicit cultural expressions such as mau ke mana, dari mana, and apa kabar. Those expressions tend to be understood not only linguistically but also culturally.